DIGITAL PASSPORTIZATION OF ARCHITECTURAL HERITAGE MONUMENTS IN SAMARKAND, BUKHARA, AND KHIVA: TECHNOLOGIES, METHODOLOGIES, AND PROSPECTS FOR PRESERVATION (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the development and implementation of digital passportization systems for architectural heritage monuments in Samarkand, Bukhara, and Khiva three UNESCO World Heritage cities in Uzbekistan. A digital passport is a comprehensive, technology-mediated documentation package that integrates historical, architectural, structural, and conservation data for a heritage monument into a unified digital record. Drawing upon Uzbek, Russian, Arabic, and Western scholarship on heritage documentation, as well as contemporary research in Heritage Building Information Modeling (HBIM), 3D laser scanning, and photogrammetry, the study analyzes the specific documentation challenges posed by Central Asian Islamic architectural heritage. The research identifies the principal monument categories requiring digital passportization in each city, evaluates the applicability of current digital documentation technologies to the distinctive material and structural characteristics of Timurid, Shaybanid, and Khivan architectural traditions, and proposes a standardized framework for digital passport creation adapted to the Uzbekistan context. The findings indicate that while significant progress has been made in individual scanning and documentation projects, a systematic, city-wide digital passportization program remains an urgent desideratum, requiring coordinated investment in technology, training, and institutional infrastructure.
Keywords: digital passport; heritage documentation; HBIM; 3D laser scanning; photogrammetry; Samarkand; Bukhara; Khiva; UNESCO World Heritage; Islamic architecture